DEFORMABILITY OF STEEL REINFORCEMENT UNDER THE ACTION OF CYCLIC LOADING (Collection of scientific works «Modern structures of metal and wood», 2022)
The aim of the article is an experimental research of the influence of low-cycle sign-constant  loading,  as  well  as  the  most  significant  design  factors  on  the  deformability  of  steel reinforcement of reinforced concrete beams. In this regard, for experimental research, the authors developed a four-factor three-level Boxing plan B4. The experimental factors of the plan were varied according to the literature review, which showed that the most significant factors are the following: the  value  of  the  relative  shear  span  a/h 0 ,  the  concrete  class  C,  the  value  (amount)  of  transverse reinforcement on the beams support sections ρ sw , the level of sign-constant loading η. The samples were tested according to the scheme of a single-span beam, alternately loaded with two centre-point forces. The number of cycles of sign-constant loading was accepted as 10.  According  to  the  results  of  the  experiment,  using  the  COMPEX  program,  adequate mathematical models of the deformations of steel reinforcement of reinforced concrete specimens-beams under the action of low-cycle sign-constant loading were derived, that reflect the influence of these  factors  both  individually  and  in  interaction  with  each  other.  Analyzing  these  models,  the features of the development of tensile reinforcement in the specified conditions, were established. In particular, the factors that have the greatest influence on deformations are the relative shear span and the  level  of  low-cycle  loading.  Thus,  with  their  increase,  the  relative  deformations  of  tensile reinforcement increase by 51% and 52%, accordingly, by series.